The investigation of elite athletes` psychological resilience - Özdemir, N. (Journal of Sport Pedagogy and Research, 2018)
The performances of the athletes can change from competition to competition under the pressure of heavy exercise and success anxiety during the season. The help obtained from sports psychology in order to minimize these fluctuations in the performance of the athlete is an important component in increasing the psychological resilience of the athlete. The aim of this study is to examine the psychological resilience of elite athletes in terms of various variables. This research is a descriptive survey model study in terms of defining psychological resilience levels of elite athletes. In this study, the Psychological Resilience Scale developed by Friborg et al. (2005) and adapted to Turkey by Basim and Çetin (2011), and the personal data form developed by the researcher for collecting personal information were used to determine the psychological resilience of elite athletes. The data of the research was collected from 147 national athletes in different branches, including 79 males and 68 females. SPSS 21.00 statistical package program was used in data analysis. Descriptive statistics, independent groups t-test, one-way variance analysis, correlation and regression analyses were used in data analysis. As a result of the study, it was found that the psychological resilience of elite athletes differed according to the athlete`s gender, sports branch, their tendency to use doping, whether the athletes make self-talk or not, but did not differ according to the athlete`s age, sports experience, and smoking and alcohol use.